2015
DOI: 10.1186/s13663-015-0423-1
|View full text |Cite
|
Sign up to set email alerts
|

A discussion on best proximity point and coupled best proximity point in partially ordered metric spaces

Abstract: In this paper we establish some best proximity point results using generalized weak contractions with discontinuous control functions. The theorems are established in metric spaces with a partial order. We view the main problem in the paper as a problem of finding an optimal approximate solution of a fixed point equation. We also discuss several corollaries and give an illustrative example. We apply our result to obtain some coupled best proximity point results.MSC: 47H10; 54H10; 54H25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…We have already noted that the main result is an actual generalization of a previous result in [4]. The methodology here is comparable with several other similar results dealing with contractive inequalities noted in [3][4][5][6][7][8][9][10]. There are possibilities of applying relation-theoretic methods to other weakly contractive mappings.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We have already noted that the main result is an actual generalization of a previous result in [4]. The methodology here is comparable with several other similar results dealing with contractive inequalities noted in [3][4][5][6][7][8][9][10]. There are possibilities of applying relation-theoretic methods to other weakly contractive mappings.…”
Section: Discussionsupporting
confidence: 84%
“…Afterwards, the idea was generalized and extended in several ways by which a large amount of literature on the fixed point theory of weakly contractive mappings was produced. Some instance of these works are [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, we have seen that the existence of the best proximity points has been investigated by several researchers by using different techniques, for example: Jleli and Samet [11] used α-ψ-proximal contraction to studied the best proximity points of single-valued mappings; Abkar and Gbeleh [12] used asymptotic cyclic contraction in their results; Abkar and Gbeleh [13] also proved the existence of best proximity points for multivalued nonself mappings satisfying contraction and nonexpansive condition along with P-property; Alghamdi et al [14] studied the best proximity point theorems in geodesic metric spaces; Choudhury et al [15] used the structure of partially-ordered metric spaces to discuss best proximity and couple best proximity points; Bari et al [16] used cyclic Meir-Keeler contraction in their discussion; Eldred and Veeramani [17] used cyclic proximal contraction to discuss the existence of best proximity point in metric space, and they further provided an algorithm to calculate a best proximity point over the structure of a uniformly-convex Banach space; Jacob et al [18] gave hybrid algorithms for nonself nonexpansive mappings and provided an iterative sequence of the algorithm, which converges to the proximity point of the mapping; Markin and Shahzad [19] studied the best proximity points of relatively u-continuous mappings; Sadiq Basha et al [20] discussed the existence of best proximity points of two mappings satisfying the min-max condition; Shatanawi and Pitea [21] used the notions of P-property and weak P-property in their best proximity theorems; Vetro [22] gave the existence and convergence theorems for best proximity points of the mappings satisfying the p-cyclic φ-contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is concluded that best proximity point theorems generalize fixed point theorems in a natural way. For more works on the existence of best proximity points, we refer [1,3,8,14,17] and references therein.…”
Section: Theorem 11 ([12]mentioning
confidence: 99%